Dispersion and socio-spatial fragmentation in the recent growth of an oil city of Argentinean Patagonia - USACH, Natalia; FREDDO, Bianca Vanesa (Papeles de Población, 2018)
The city of Comodoro Rivadavia in Argentina Patagonia has grown historically dispersed from the location and consolidation of settlements of workers around the broad areas of oil exploitation. This paper aims to recognize and characterize the recent patterns of urban growth in this city using complementary to quantitative data from official sources, own surveys and a technique of observation and analysis of satellite images. This allows identify recent changes in the occupation of space. The results confirm that the dispersed expansion of the city tends to deepen with strong connotations of social and spatial fragmentation.